Laras Slendro In Traditional Music Gamelan Banyuwangi Changes (Universitas Negeri Semarang, 2022)
A traditional music group from the Banyuwangi region with unique qualities is called Gamelan Banyuwangi. The peculiar laras known as the slendro sliring that distinguishes the Banyuwangi gamelan from other gamelan is one of its distinguishing features. The laras slendro sliring, however, became less common as time went on due to changes. This study set out to identify the variables that affected how the laras slendro changed in relation to the Banyuwangi gamelan. Descriptive qualitative research methodology was employed in this study. The laras on the Banyuwangi gamelan serve as the study's formal and material objects, respectively, together with the notion of change. Secondary information was gathered from records, such as old music videos and some pictures of previous forms of gamelan music. Data collection techniques used in this study include observation, interviews, and document studies. To get the validity of the data the author triangulated the sources. The analysis technique used by the author includes data reduction, data presentation, and drawing conclusions. The results of the study, there are two factors that affect the change in the laras of the Banyuwangi gamelan slendro, namely changes in evolution and acculturation. Evolutionary changes occur in the decrease in the tone of the laras slendro sliring to the slendro that is used today because the younger generation cannot follow the use of the laras slendro sliring so there is an evolution in Banyuwangi gamelan music. Second, there are changes due to acculturation factors that occur during tuning, so Banyuwangi gamelan craftsmen use standard Western music tuners to make tuning easier.